Pengaruh Trend Dan Brand Image Terhadap Keputusan Pembelian Dengan Gaya Hidup Sebagai Variabel Intervening Pada Pelanggan Jilbab Merek Bella Square Di Kabupaten Kolaka - Hijriyanti, Sri Ainun; Effendi, Ahmad; Abdullah, Wahidah (Study of Scientific and Behavioral Management, 2023)
ABSTRACT The aim of this study was to determine the effect of trend and brand image on purchasing decisions intervening by lifestyle on customers of the Bella Square hijab brand in Kolaka district. Structural Equation Modeling (SEM) with the help of the SmartPLS application version 3.0 for Windows is used in this research data analysis technique to examine trends, brand image, purchasing decisions, and style and lifestyle as intervening variables The results of this study indicate that trend has a negative and insignificant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, trend has a positive and significant effect on lifestyle, brand image has a positive and significant effect on lifestyle, lifestyle has a positive and significant effect on purchasing decisions, trend has a positive and significant effect on purchasing decisions through lifestyle as an intervening variable, brand image has a positive and significant effect on purchasing decisions through lifestyle as an intervening variable for customers of the Bella Square hijab brand. Keywords: Trend, Brand Image, Lifestyle and Purchase Decision